Hubungan Antara Kompetensi Pedagogik Guru dan Motivasi Belajar Siswa PAI Kelas IX di Madrasah Tsanawiyah Al-Hidayah Citaringgul Kab Bogor - M.Rifqi Ansorillah Supiyan; Sri Nurul Milla (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
The importance of teacher pedagogical competence which includes the teacher's ability to manage learning such as understanding students, designing learning and evaluating learning in grades can influence student motivation. The aims of this research are: (1) to find out the relationship between teacher pedagogical competence at MTS Al-Hidayah Citaringgul (2) to find out students' awareness of learning motivation at MTS Al-Hidayah Citaringgul (3) to find out whether teachers' pedagogical competence and learning motivation influence on students at MTS Al-Hidayah Citaringgul, Bogor Regency. This research uses quantitative methods using surveys as a data collection technique. Teacher pedagogical competency questionnaires and learning motivation questionnaires were distributed to 152 class IX students at Mts Al-Hidayah Citaringgul. The results of this research are: (1) PAI pedagogical competence at MTS Al-Hidayah Citaringgul is included in the quite good category with a score of 72.13 (2) The learning motivation of class IX students at MTS Al-Hidayah Citaringgul is included in the very good category with a score of 68.85 (3) There is no significant relationship between teacher pedagogical competence and learning motivation of class IX students at the Al-Hidawiyah Al-Hidawiyah Madrasah, Citaringgul, Bogor Regency.